#2**+1 **

To do this problem, evaluate n at the values from the positive integers n=3 to n=7

When n=3:

\(2n+3\) | Plug in the appropriate value for n, which is 3, in this case. |

\(2*3+3\) | |

\(6+3\) | |

\(9\) | |

Now, let's evaluate it for n=4:

\(2n+3\) | Plug in n=4 |

\(2*4+3\) | |

\(8+3\) | |

\(11\) | |

n=5:

\(2n+3\) | Replace all instances of n with 5 |

\(2*5+3\) | |

\(10+3\) | |

\(13\) | |

n=6:

\(2n+3\) | Plug in 6 for n |

\(2*6+3\) | |

\(12+3\) | |

\(15\) | |

Now, I do not have to evaluate 7 as I can infer, based on the information above, that the next value in the series will be the sum of the last number in the series and 2. Therefore, 2n+3 when n=7, the expression evaluates to 17.

Now, our last step is too add the series together:

\(9+11+13+15+17\) | Figure out what this evaluates to. Of course, with addition you can add in whatever order you'd like. I'll use this property to my advantage to ease calculation. |

\(20+13+15+17\) | |

\(20+30+15\) | |

\(50+15\) | |

\(65\) | |

TheXSquaredFactor Aug 4, 2017